Studi Eksperimental Efektivitas Soygurt Kacang Hijau Sari Kurma sebagai Terapi Adjuvan pada Tikus Diabetes Tipe 2 - Jannah, Miftakhul; Setyo Sri Rahardjo; Ratih Puspita Febrinasari (Nutriology : Jurnal Pangan, Gizi, Kesehatan, 2025)
Diabetes Mellitus (DM) is a metabolic disorder characterized by hyperglycemia resulting from abnormalities in insulin secretion, insulin action, or both. Management of DM involves pharmacological therapy, nutritional intervention, and physical activity. Recently, adjuvant therapies based on functional foods containing probiotics and natural bioactive compounds have gained increasing attention, one of hich is Soygurt. When combined with mung beans and date juice as a natural sweetener, soygurt has the potential to improve glucose metabolism and influence body weight. This study aimed to analyze the effects of mung bean soygurt with date palm extract as an adjuvant therapy in a type 2 diabetes mellitus (T2DM) mouse model, focusing on body weight and fasting blood glucose levels. The research employed a pre-posttest control group experimental design using male Wistar rats (Rattus norvegicus) induced with T2DM. A total of 30 rats were divided into six groups: healthy control, negative control, positive control (metformin 9 mg/kgBW/day), and three treatment groups receiving different doses of soygurt (1 ml, 2 ml, and 3 ml) combined with metformin for 28 days. The results showed a significant increase in body weight across all groups (p < 0.05), and a significant decrease in fasting blood glucose in the positive control and treatment groups (P1, P2, P3) (p < 0.05). Conclusion, the study shows that mung bean soygurt with date extract has the potential as an adjuvant therapy for type 2 diabetes mellitus.